The Influence of Interface Structure on the Electrical Conductivity of Graphene Embedded in Aluminum Matrix. Issue 13 (22nd May 2019) - Cao, Mu; Luo, Yongzhi; Xie, Yiqun; Tan, Zhanqiu; Fan, Genlian; Guo, Qiang; Su, Yishi; Li, Zhiqiang; Xiong, Ding‐Bang
Abstract: Graphene is considered a promising reinforcement to improve the electrical conductivity of metals because of its excellent intrinsic electrical conductivity. However, graphene/Al matrix composites with enhanced electrical conductivity have not yet been reported. In this work, it is attempted to understand the factors influencing the electrical conductivity of graphene embedded in an Al matrix by adjusting the interfacial structure and composition. By sandwiching graphene (Gr) or graphene oxide (GO) with either pristine or passivated Al foils, three kinds of typical composite interfaces are successfully fabricated: pristine‐Al/Gr/pristine‐Al (Al/Gr/Al), passivated‐Al/Gr/passivated‐Al (Al‐O/Gr/O‐Al), and pristine‐Al/GO/pristine‐Al (Al/GO/Al). As revealed by electrical current mapping of the interfacial area, the Gr layer in the sandwiched Al/Gr/Al composite shows an electrical conductivity ≈70 times higher than that of the surrounding Al matrix. Gr with a high electrical conductivity is not observed in the Al‐O/Gr/O‐Al and Al/GO/Al composites. The mechanisms are understood by microstructural characterizations and first‐principle calculations. The results indicate that high‐quality Gr and metal–Gr contact are simultaneously needed to improve the electrical conductivity of Al by incorporating graphene. Abstract : By sandwiching chemical vapor deposition graphene with pristine Al foils, the electrical conductivity of graphene can be enhanced by about 400 times, which is ≈70 times high than that of the pure aluminum matrix. The results indicate that ultrahigh electrical conductivity can be realized in graphene/aluminum matrix composites with an optimized interface structure and high enough graphene fraction.